An analysis of microstructure and impression creep response of squeeze-cast AZ91–xBi–ySr alloys. Issue 6 (12th April 2020) - Majhi, Jichil; Das, Tanmoy; Basu, A.; Mondal, A. K.
ABSTRACT: The present investigation deals with the microstructural modification following the Bi + Sr additions to the squeeze-cast AZ91 alloy and its effect on impression creep response. The Bi + Sr additions form the Al4 Sr and Sr2 Bi phases besides the α-Mg and β-Mg17 Al12 phases, and improves creep resistance of the AZ91 alloy. The AZ91 + 1.0Bi + 0.5Sr alloy reveals the best creep resistance among the alloys. The stress exponent and the activation energy values of all the alloys are in the range of 4–7 and 100.2–112.7 kJ mol −1, respectively, depicting the pipe diffusion-controlled dislocation creep is the governing creep mechanism. The post-creep microstructural study confirms several dislocations pile-ups around the Al4 Sr and Sr2 Bi phases resulting in improved creep resistance of the modified AZ91 alloys.